Exome variant prioritization in a large cohort of hearing-impaired individuals indicates IKZF2 to be associated with non-syndromic hearing loss and guides future research of unsolved cases - Hedwig M. Velde; Maryam Vaseghi-Shanjani; Jeroen J. Smits; Gayatri Ramakrishnan; Jaap Oostrik; Mieke Wesdorp; Galuh Astuti; Helger G. Yntema; Lies Hoefsloot; Cris P. Lanting; Martijn A. Huynen; Anna Lehman; et al. (Human Genetics, 2024)
Although more than 140 genes have been associated with non-syndromic hereditary hearing loss (HL), at least half of the cases remain unexplained in medical genetic testing. One reason is that pathogenic variants are located in ‘novel’ deafness genes. A variant prioritization approach was used to identify novel (candidate) genes for HL. Exome-wide sequencing data were assessed for subjects with presumed hereditary HL that remained unexplained in medical genetic testing by gene-panel analysis. Cases in group AD had presumed autosomal dominantly inherited HL (n = 124), and in group AR, presumed autosomal recessive HL (n = 337). Variants in known and candidate deafness genes were prioritized based on allele frequencies and predicted effects. Selected variants were tested for their co-segregation with HL. Two cases were solved by variants in recently identified deafness genes ( ABHD12 , TRRAP ). Variant prioritization also revealed potentially causative variants in candidate genes associated with recessive and X-linked HL. Importantly, missense variants in IKZF2 were found to co-segregate with dominantly inherited non-syndromic HL in three families. These variants specifically affected Zn 2+ -coordinating cysteine or histidine residues of the zinc finger motifs 2 and 3 of the encoded protein Helios. This finding indicates a complex genotype–phenotype correlation for IKZF2 defects, as this gene was previously associated with non-syndromic dysfunction of the immune system and ICHAD syndrome, including HL. The designed strategy for variant prioritization revealed that IKZF2 variants can underlie non-syndromic HL. The large number of candidate genes for HL and variants therein stress the importance of inclusion of family members for variant prioritization.

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Invertebrate metal accumulation and toxicity from sediments affected by the Mount Polley mine disaster - Gregory G. Pyle; Raegan D. Plomp; Lauren Zink; Jaimie L. Klemish (Environmental Science and Pollution Research, 2022)

Correction to: Exploring the missing heritability in subjects with hearing loss, enlarged vestibular aqueducts, and a single or no pathogenic SLC26A4 variant - Jeroen J. Smits; Suzanne E. de Bruijn; Cornelis P. Lanting; Jaap Oostrik; Luke O’Gorman; Tuomo Mantere; M. F. van Dooren; S. G. Kant; H. H. W. de Gier; E. H. Hoefsloot; M. P. van der Schroeff; L. J. C. Rotteveel; et al. (Human Genetics, 2022)

Exploring the missing heritability in subjects with hearing loss, enlarged vestibular aqueducts, and a single or no pathogenic SLC26A4 variant - Jeroen J. Smits; Suzanne E. de Bruijn; Cornelis P. Lanting; Jaap Oostrik; Luke O’Gorman; Tuomo Mantere; M. F. van Dooren; S. G. Kant; H. H. W. de Gier; E. H. Hoefsloot; M. P. van der Schroeff; L. J. C. Rotteveel; et al. (Human Genetics, 2022)
Pathogenic variants in SLC26A4 have been associated with autosomal recessive hearing loss (arHL) and a unilateral or bilateral enlarged vestibular aqueduct (EVA). SLC26A4 is the second most frequently mutated gene in arHL. Despite the strong genotype–phenotype correlation, a significant part of cases remains genetically unresolved. In this study, we investigated a cohort of 28 Dutch index cases diagnosed with HL in combination with an EVA but without (M0) or with a single (M1) pathogenic variant in SLC26A4 . To explore the missing heritability, we first determined the presence of the previously described EVA-associated haplotype (Caucasian EVA (CEVA)), characterized by 12 single nucleotide variants located upstream of SLC26A4 . We found this haplotype and a delimited V1-CEVA haplotype to be significantly enriched in our M1 patient cohort (10/16 cases). The CEVA haplotype was also present in two M0 cases (2/12). Short- and long-read whole genome sequencing and optical genome mapping could not prioritize any of the variants present within the CEVA haplotype as the likely pathogenic defect. Short-read whole-genome sequencing of the six M1 cases without this haplotype and the two M0/CEVA cases only revealed previously overlooked or misinterpreted splice-altering SLC26A4 variants in two cases, who are now genetically explained. No deep-intronic or structural variants were identified in any of the M1 subjects. With this study, we have provided important insights that will pave the way for elucidating the missing heritability in M0 and M1 SLC26A4 cases. For pinpointing the pathogenic effect of the CEVA haplotype, additional analyses are required addressing defect(s) at the RNA, protein, or epigenetic level.

Estimating EEG Source Dipole Orientation Based on Singular-value Decomposition for Connectivity Analysis - M. Rubega; M. Carboni; M. Seeber; D. Pascucci; S. Tourbier; G. Toscano; P. Van Mierlo; P. Hagmann; G. Plomp; S. Vulliemoz; C. M. Michel (Brain Topography, 2019)

ABCC6 and pseudoxanthoma elasticum - Arthur A. B. Bergen; Astrid S. Plomp; Xiaofeng Hu; Paulus T. V. M. de Jong; Theo G. M. F. Gorgels (Pflügers Archiv - European Journal of Physiology, 2007)